2013
DOI: 10.1021/jf402539m
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Deactivation Kinetics of Pseudomonas fluorescens Lipase Entrapped in AOT/Isooctane Reverse Micelles

Abstract: Thermostability of the lipase (EC 3.1.1.3) was found to be increased by the enzyme-entrapment in 50 mM AOT/isooctane reverse micelles. The half-life (15.75 h) of Pseudomonas fluorescens lipase entrapped in reverse micelles at 70 °C was 9.72- and 11.41-fold longer than those solubilized in a glycerol pool or in 10 mM phosphate buffer (pH 8.0), respectively. The enzyme deactivation model considering a two-step series-type was employed, and deactivation constants for the second step (k₂) at all temperatures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…After fitting the data, the free and immobilized lipase are accorded with a two‐step series‐type enzyme model [Eq. (1)]: E0k1E1k2E2 …”
Section: Resultsmentioning
confidence: 99%
“…After fitting the data, the free and immobilized lipase are accorded with a two‐step series‐type enzyme model [Eq. (1)]: E0k1E1k2E2 …”
Section: Resultsmentioning
confidence: 99%
“…The slowdown of reaction rate could be caused by enzyme deactivation, 22,23 product inhibition 24 and attainment of chemical equilibrium 13 as others have demonstrated. Increase in C E can cause high cost even if Y is improved.…”
Section: Kinetic Study On the Effect Of Enzyme Loadingmentioning
confidence: 95%
“…16 Further parameters that influence the enzyme activity are the pH value and the temperature. Usually, the enzyme shows highest activity only for one pH value as shown by Park et al 21 and Fei et al 17 Both researchers also investigated enzyme activity as a function of temperature. For temperatures above 40 °C, enzyme denaturation is observed and activity decreases with increasing temperature.…”
Section: Biocatalysismentioning
confidence: 99%
“…For temperatures above 40 °C, enzyme denaturation is observed and activity decreases with increasing temperature. However, Park et al 21 showed that the enzyme is less temperature sensitive in w/o-microemulsions, because the surfactant suppresses the interaction between the enzyme and the organic solvent. Even if the reactions are carried out in w/o-microemulsions, different groups have shown that the reaction can be described by applying the Michaelis-Menten kinetics.…”
Section: Biocatalysismentioning
confidence: 99%